2023
DOI: 10.1002/adhm.202302640
|View full text |Cite|
|
Sign up to set email alerts
|

Evaluation of Reactive Oxygen Species Scavenging of Polydopamine with Different Nanostructures

Yuyi Zheng,
Xiaojie Chen,
Qi Zhang
et al.

Abstract: Reactive oxygen species (ROS) play an important role in cellular metabolism and many oxidative stress‐related diseases, while excessive accumulation of ROS will lead to genetic changes in cells and promote the occurrence of inflammatory diseases or cell death. Nature‐inspired polydopamine (PDA) with tailored nanostructures emerges as an ROS scavenger and is considered as an effective approach to inflammation‐related diseases. However, the effects of nanoparticle structure on PDA scavenging efficacy and efficie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 38 publications
0
9
0
Order By: Relevance
“…Next, the cellular ROS scavenging capability of HBPSi-Met was tested. Initially, a cellular lesion model was established by incubating NCM460 cells with 1 μg/mL lipopolysaccharide (LPS) for 24 h. , Then, live/dead staining was conducted to test the ROS scavenging ability of HBPSi-Met, in which the red and green fluorescence represented dead cells and live cells, respectively. As depicted in Figure I, both red and green fluorescence were simultaneously monitored in the buffer treated LPS damage cells, attributing to the oxidative stress-induced cell damage by LPS activation.…”
Section: Resultsmentioning
confidence: 99%
“…Next, the cellular ROS scavenging capability of HBPSi-Met was tested. Initially, a cellular lesion model was established by incubating NCM460 cells with 1 μg/mL lipopolysaccharide (LPS) for 24 h. , Then, live/dead staining was conducted to test the ROS scavenging ability of HBPSi-Met, in which the red and green fluorescence represented dead cells and live cells, respectively. As depicted in Figure I, both red and green fluorescence were simultaneously monitored in the buffer treated LPS damage cells, attributing to the oxidative stress-induced cell damage by LPS activation.…”
Section: Resultsmentioning
confidence: 99%
“…[ 25 ] PDA, rich in reducing groups like phenol and catechol, exhibits excellent redox capacity and serves as an effective ROS scavenger by donating free radical electrons. [ 26 ] In particular, mPDA NPs, known for their enhanced active site accessibility, have garnered considerable attention in this context. [ 27 ]…”
Section: Resultsmentioning
confidence: 99%
“…Besides, PDA-based nanocomposites have a wide variety of structures, including core–shell, double-sided, hollow, and mesoporous structure, especially the erythrocyte-like mesoporous nanobowl, which provides not only sufficient space for drug loading but also more conducive to the uptake of the drug-carrying system by cells . In addition, Zheng reported that the mesoporous PDA has the highest ROS-scavenging capability . Inspired by this, the ultrasmall CeO 2 NPs with multienzyme activity can be grown in situ on nonenzyme activity mPDA NBs due to the chelating property of mPDA for effective ROS elimination.…”
Section: Introductionmentioning
confidence: 99%
“…38 In addition, Zheng reported that the mesoporous PDA has the highest ROS-scavenging capability. 39 Inspired by this, the ultrasmall CeO 2 NPs with multienzyme activity can be grown in situ on nonenzyme activity mPDA NBs due to the chelating property of mPDA for effective ROS elimination. In addition, due to the large internal and external surfaces and pores, different anti-inflammatory drugs can be loaded into the mPDA NBs.…”
Section: ■ Introductionmentioning
confidence: 99%